Comparative study of ternary graphite-potassium-metal (M = Tl, Hg, Au) intercalation compounds. (November 2015) - Cahen, Sebastien; Fauchard, Mélissa; Lagrange, Philippe; Hérold, Claire
Abstract : Potassium–thallium, potassium–mercury, and potassium–gold alloys can be intercalated into graphite, leading to the formation of poly-layered ternary compounds. Different ways of synthesis are involved for the preparation of the corresponding Graphite Intercalation Compounds (GICs). The as-prepared bulk GICs are described in a comparative study, regarding their chemical formula, their formation mechanism, and their structural and superconducting properties. Analogies and differences are pointed out. [TANSO 2015 (No. 268), 145–53.]